2017
DOI: 10.1007/s00132-017-3450-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct repair of the sagittal band for extensor tendon subluxation caused by finger flicking

Abstract: Realignment of the extensor tendon and direct repair of the superficial layer of the sagittal band to the extensor digitorum communis (EDC) tendon is recommended as a treatment option in patients with chronic MCP extensor tendon subluxation, as well as for acute MCP extensor tendon subluxation in patients that have failed or could not maintain conservative treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Of these, 10 articles were excluded due to inclusion of less than 5 treated digits, 4 were review articles, 4 were descriptions of surgical techniques without any reported patient outcome data, 7 described treatment and outcomes for MCP capsular tears or collateral ligament injuries, and 1 included patients with rheumatoid arthritis. A total of 17 articles were included in the final systematic review and qualitative synthesis 1,3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 10 articles were excluded due to inclusion of less than 5 treated digits, 4 were review articles, 4 were descriptions of surgical techniques without any reported patient outcome data, 7 described treatment and outcomes for MCP capsular tears or collateral ligament injuries, and 1 included patients with rheumatoid arthritis. A total of 17 articles were included in the final systematic review and qualitative synthesis 1,3,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were single-center retrospective case series (Sackett level 4) with the defined inclusion and exclusion criteria, 13,14,17,22 and the remaining 13 were retrospective case reports (Sackett level 4). According to the SEQES scores, only 4 articles were considered to be of moderate quality (scores 17-32), 13,14,17,22 with the remaining being ranked as low-quality articles (scores 0-16). The mean SEQES score was 15 (range, 12-21), with no article achieving a high-quality rating (Figure 2).…”
Section: Study Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Various surgical methods are known for the treatment of the sagittal band, and among them, the classic surgical method is to suture the tendon with the fiber of the damaged sagittal band. Hong et al [7] successfully treated 26 type II and III patients with spontaneous ruptures through direct repair. Tendon slip or juncturae tendinum is mainly used when direct repair is not possible due to the tissue gap or chronicity of the damaged sagittal band [8,9].…”
Section: Discussionmentioning
confidence: 99%